DILEMMAS AND VULNERABILITIES: THE REALITY OF MANACAPURU-AM FROM 2018 TO 2022 - de Moraes, João Batista Flores; Gomes, Fábio Alves (Seven Editora, 2025)
The objective of this article is to present the results of research carried out in the records of Police Inquiries of DEAM, Comarca de Manacapuru-AM, produced in the period 2018/2022, with the purpose of characterizing patrimonial violence, profiling the aggressor, victim and analyzing the victim's narrative. The historical-dialectical method was used for the analysis of an integrative review of the scientific literature and documentary research. The approach was qualitative. The results of the documentary research indicated the average profile of victim and aggressor at the locus. The analysis of the victims' narratives indicated the existence of multifaceted patrimonial violence that makes them vulnerable. An increase in the demand for protective measures was observed, indicating a reduction in tolerance to domestic violence.DOI: https://doi.org/10.56238/sevened2025.029-039